Strengthening a Learning-Centered College/University Classroom in Ethiopia: Current Wisdom in Teacher Professional Development - Negassi, Reda Darge (Bahir Dar Journal of Education, 2016)
The purpose of this article is to show increased concern in the new ways of structuring schooling in college/university classroom to address the learning needs of students. Accordingly, the cognitive view of motivation serves as a conceptual framework to understand studentsâ€™ learning. In the past decade, we have seen the Higher Diploma Programme (HDP), which was developed as a result of the study into the quality and effectiveness of teacher education in Ethiopia focused on teaching techniques in Ethiopian college/university classrooms, a movement that emphasizes active learning, practicum, action research, reflection, and managing learning. Relatively little emphasis was paid on studentÂ´s motivational beliefs that are presumed to occur in instructional settings. The reform seemed to reflect time-worn assumptions about learners and learning that may limit teacherÂ´s ways of thinking about the role of the college/university student in the classroom (refer appendix). Fortunately, this state of concern is very much similar with the state of classroom learning in the early 1980s. This intensive focus on teaching techniques, but largely ignoring studentsâ€™ motivational beliefs that occur in instructional settings may lead teachers to the conclusion that a focus merely on instruction is one-sided. Hence, efforts must be made to strengthen a more balanced discourse that emphasizes the subtle nuances and complexities of learning within any discussion of teaching. One change that could begin to maximize students` learning would strengthen â€œlearning-centered" classroom. To strengthen â€œlearning-centeredâ€ classroom the theoretical review focuses on how studentsâ€™ motivational beliefs and teachersâ€™ behavior/instructional factors influence studentsâ€™ motivation to learn. The review concluded that a learning-centered perspective regards the classroom as a dynamic setting where pedagogical practices and learnersâ€™ motivational beliefs meet and where the quality of this interaction influences the learning needs of students that are presumed to occur in college classrooms. Presumably if the next generation of teachers designed their classroom environments to be in accord with these recommendations, future generations of university/college students would be much more motivated than the current one. Hence to achieve this expectation, a continuous professional development programme for college/university teachers which focuses on student motivational beliefs is urgently needed. Action to strengthened learning-centred classroom is vital to improve the quality of teacher professional development in Ethiopia. Finally, the review has implication concerns voiced the current wisdom about teacher professional development in Ethiopia.